A polymorphic variant in telomere maintenance is associated with worrisome features and high-risk stigmata development in IPMNs. (8th June 2022) - Giaccherini, Matteo; Gentiluomo, Manuel; Arcidiacono, Paolo Giorgio; Falconi, Massimo; Testoni, Sabrina Gloria Giulia; Apadula, Laura; Lauri, Gaetano; Di Franco, Gregorio; Fatucchi, Lorenzo Maria; Petrone, Maria Chiara; Corradi, Chiara; Crippa, Stefano; et al.
Abstract: Intraductal papillary mucinous neoplasms (IPMNs) are nonobligatory precursor lesions of pancreatic ductal adenocarcinoma (PDAC). The identification of molecular biomarkers able to predict the risk of progression of IPMNs toward malignancy is largely lacking and sorely needed. Telomere length (TL) is associated with the susceptibility of developing cancers, including PDAC. Moreover, several PDAC risk factors have been shown to be associated with IPMN transition to malignancy. TL is genetically determined, and the aim of this study was to use 11 SNPs, alone or combined in a score (teloscore), to estimate the causal relation between genetically determined TL and IPMNs progression. For this purpose, 173 IPMN patients under surveillance were investigated. The teloscore did not show any correlation, however, we observed an association between PXK -rs6772228-A and an increased risk of IPMN transition to malignancy (HR = 3.17; 95%CI 1.47–6.84; P  = 3.24 × 10 -3 ). This effect was also observed in a validation cohort of 142 IPMNs even though the association was not statistically significant. The combined analysis was consistent showing an association between PXK -rs6772228-A and increased risk of progression. The A allele of this SNP is strongly associated with shorter LTL that in turn have been reported to be associated with increased risk of developing PDAC. These results clearly highlight the importance of looking for genetic variants as potential biomarkers in this setting in order to further our understanding the etiopathogenesis of PDAC and suggest that genetically determined TL might be an additional marker of IPMN prognosis. Abstract : A polymorphic variant in a telomere length regulating gene (PXK) is associated with an increased chance of intraductal papillary mucinous neoplasms (IPMNs) progression. This association has never been reported before and highlights the importance of germline genetics in IPMN research. Graphical Abstract: